Respon Peternak terhadap Teknologi Pembuatan Suplemen Katalitik untuk Kambing di Kota Kendari - Agustina, Dian (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This research was aimed to study the response of stock farmer on a made catalytic supplement for goat. The sample size on this research has taken by the census of a method that is used the all number of population as the sample about 20 people. The result of data analysis indicates that the all-stock farmer has given positive of respond on made catalytic supplement of technology, likely most 20 people (100%) declare that the material is simple, most 15 people have declared that the material process is easy, and the last 20 people (100%) has declared that knowledge regarded material of process is most utility. Therefore, disseminating regarded technology of the catalytic supplement made is more significant to do.